H2AFZ Is a Prognostic Biomarker Correlated to TP53 Mutation and Immune Infiltration in Hepatocellular Carcinoma - Dong, Mingwei; Chen, Jing; Deng, Yiran; Zhang, Danying; Dong, Ling; Sun, Dalong (Frontiers in Oncology, 2021)
H2A family member Z (H2AFZ) is a highly conserved gene encoding H2A.Z.1, an isoform of histone variant H2A.Z, and is implicated in cancer. In this study, we report that overexpression of H2AFZ is associated with tumor malignancy and poor prognosis in HCC patients. Functional network analysis suggested H2AFZ mainly regulates cell cycle signaling and DNA replication via pathways involving several cancer-related kinases and transcription factor E2F1. Further studies revealed that H2AFZ overexpression is related to TP53 mutation and immune infiltrations in HCC. Moreover, we found that H2AFZ is co-expressed with immune checkpoint genes, including CD274 (PD-L1), CTLA-4, HAVCR2 (TIM3), LAG3, PDCD1 (PD-1) and TIGIT (VSIG9) in HCC, indicating H2AFZ-overexpressed HCC patients may be sensitive to immune checkpoint blockades (ICBs). Integrated analysis suggested H2AFZhigh/TP53mut patients has the worst prognosis and the greatest risk of tumor recurrence, while is more likely to be sensitive to ICBs. These findings indicate that the H2AFZ possess potential value as a novel prognostic indicator for HCC patients and is correlated with immune infiltration in HCC, laying a foundation for future study of HCC investigation and intervention.